Goddesses of Akragas : A Study of Terracotta Votive Figurines from Sicily. - Rooijen, Gerrie van, 1985- (Sidestone Press, 2021)
The terracotta figurines from Akragas (Agrigento) with their chubby faces, splendid furniture, and rich adornments, depict a prosperous life in the late sixth and early fifth century BCE. The extensive jewellery on the figurines contains strikingly large fibulae appliques fastening pectoral chains with several sorts of pendants. They are modelled after existing items. The form of the jewellery items changed fast, influenced by different peoples and changing fa.